A bespoke sleep monitoring and sleep hygiene intervention improves sleep in an U18 professional football player: A case study - Edinborough, L.; Hill, J.; Jarvis, M.; Bruce-Low, S.; Pedlar, C. R. (Journal of Sports Sciences, 2023)
This case study reports on a professional football player (age: 17.6 years) who was referred for sleep monitoring and intervention after reporting excessive night-time awakenings. The player undertook a series of subjective sleep assessments and objective sleep monitoring (activity monitor). Based on the data presented, a sleep hygiene intervention was prescribed. Numerical comparisons were made between pre-intervention (Pre) and post-intervention (Post) values. Objective values were also compared to reference data from a similarly aged professional cohort from the same club (n = 11). Wake episodes per night (Pre: 7.9 ± 3, Post: 4.5 ± 1.9; -43%) and wake after sleep onset (WASO; Pre: 74.3 ± 31.8 mins, Post: 50.0 ± 22.8 mins, -33%) were improved from Pre to Post. Compared to the reference data, mean wake episodes per night (Pre: 7.9 ± 3.0, reference: 4.6 ± 2.6; -42%) and WASO (Pre: 74.3 ± 31.8 mins, reference: 44.3 ± 36.5 mins; -40%) were all lower compared to Pre levels. Whilst causality cannot be proven, we observed multiple sleep metrics improving following an intervention. This provides a potential framework for practitioners looking to provide targeted sleep assessment and intervention.